2021
DOI: 10.1007/s11562-021-00475-1
|View full text |Cite
|
Sign up to set email alerts
|

Faith and fandom: young Indonesian Muslims negotiating K-pop and Islam

Abstract: Contemporary scholars in the intersecting field of popular culture and Islamic studies have argued for the importance of researching the ways Muslims engage with, make meaning of, and (re)produce different forms of popular culture. The current study continues these endeavours by examining a hitherto understudied form of popular culture in this field, namely, Korean popular culture. As previous studies on Islam and popular culture have drawn attention to, the focus of this study is on how this specific form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
2
0
2
Order By: Relevance
“…Similarly, a study by Khan et al (2018) showed that some South Asian Muslims celebrate holidays from the dominant different religion. Similar behaviour was also found in Elaskary's (2018) and Mulya's (2021) studies. They discovered that some Muslim consumers may assimilate their behaviour by consuming Korean products without considering their halal status or even adapting to Korean fashion and dressing style.…”
Section: Types Of Muslim Consumers Based On Acculturation Modessupporting
confidence: 88%
See 2 more Smart Citations
“…Similarly, a study by Khan et al (2018) showed that some South Asian Muslims celebrate holidays from the dominant different religion. Similar behaviour was also found in Elaskary's (2018) and Mulya's (2021) studies. They discovered that some Muslim consumers may assimilate their behaviour by consuming Korean products without considering their halal status or even adapting to Korean fashion and dressing style.…”
Section: Types Of Muslim Consumers Based On Acculturation Modessupporting
confidence: 88%
“…Mulya (2021) emphasised that religion is not a barrier for Muslim consumers in Indonesia to consume Korean products. Especially Muslim women, many of whom wear veils while emulating Korean culture do not evade social norms or Islamic religious doctrines.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terdiri dari berbagai genre musik seperti Pop, Hip-Hop, R &B, dan Dance Pop. Dengan terus berkembangnya budaya populer, khususnya industri musik K-Pop, pendapatan tahunan mencapai 5 miliar USD (Wijaya Mulya, 2021). Istilah "K-Pop" juga dapat mengacu pada lagu, genre musik, dan tarian yang diciptakan oleh seorang idola, baik dalam grup maupun secara individu (Yenti et al, 2022).…”
Section: Pendahuluanunclassified
“…Oleh karenanya, dalam proses masuknya budaya asing, khususnya K-pop ke Indonesia, akan memiliki kesenjangan budaya dan pertentangan nilai yang dipengaruhi oleh nilai-nilai Islam yang berkembang di masyarakat Indonesia. Dalam hal ini, K-pop sering dikaitkan dengan seksualitas dan tarian yang menjadi keprihatinan moral Islam (Mulya, 2021). Pertentangan terhadap K-pop lainnya dapat dilihat dengan adanya anggapan bahwa instrumen-instrumen dalam musik populer Korea Selatan sering ditujukan sebagai sebuah bentuk kampanye gaya hidup lesbian, gay, biseksual dan transgender (LGBT) karena adanya kedekatan fisik (skinship) di antara artis Korea sesama jenis.…”
Section: Dinamika Perkembangan K-pop DI Tiongkok Dan Indonesiaunclassified